Acute hyponatremia after aneurysmal subarachnoid hemorrhage: Frequency, treatment, and outcome. (June 2021) - Kieninger, Martin; Kerscher, Christina; Bründl, Elisabeth; Bele, Sylvia; Proescholdt, Martin; Zeman, Florian; Graf, Bernhard; Schmidt, Nils-Ole; Schebesch, Karl-Michael
Highlights: Hyponatremia is observed often after aneurysmal subarachnoid hemorrhage. More than 50% of the patients had experienced at least one episode of hyponatremia. The occurrence of hyponatremia was not correlated with the severity of the bleeding. Poor outcome was lower in patients with occurrence of moderate hyponatremia. Outcome was not correlated with the lowest serum sodium concentration. Patients treated with tolvaptan showed a better outcome 6 months after the bleeding. Abstract: We retrospectively examined the course of serum sodium levels in 180 patients with acute aneurysmal subarachnoid hemorrhage (SAH) who had been admitted to the anesthesiologic-neurosurgical intensive care unit of the University Medical Center Regensburg, Germany, between January 2014 and December 2018. Each patient file was analyzed regarding the frequency and intensity of hyponatremic episodes and the administered medication. At admission to the intensive care unit (ICU), 18 patients had shown initial hyponatremia (<135 mmol/L) and 4 patients hypernatremia (greater than145 mmol/L). 88 (48.9%) of the 158 patients with normal serum sodium levels developed at least one hyponatremic episode during ICU treatment. The number of hyponatremic episodes was similar between patients with higher-grade and lower-grade aneurysmal SAH (P = 0.848). At the end of ICU treatment, outcome did not differ between patients with and without hyponatremia (40/88, 45.5% vs. 38/70, 54.3%, P = 0.270). At 6 months after SAH, however, good outcome (Glasgow outcome scale, GOS 4–5) was more frequently observed in patients with hyponatremia (26/88, 29.5% vs. 32/70, 45.7%, P = 0.036). Medication with sodium chloride, fludrocortisone, or tolvaptan was initiated in 75.4% patients with mild hyponatremia (130–134 mmol/L) and in 92.9% with moderate hyponatremia (125–129 mmol/L). At 6 months after SAH, patients treated with tolvaptan had a lower rate of poor outcome than patients who had not received tolvaptan (1/14, 7.1% vs. 25/74, 33.8%, P = 0.045). In patients with acute aneurysmal SAH and hyponatremic episodes, consequent treatment of hyponatremia prevented impaired outcome. Because administration of tolvaptan rapidly normalized serum sodium levels, this therapy seems to be a promising treatment approach.